Geometric simulation of perovskite frameworks with Jahn-Teller distortions: applications to the cubic manganites. - Sartbaeva, A; Wells, SA; Thorpe, M; Bozin, E; Billinge, S (2006)
A new approach is presented for modeling perovskite frameworks with disordered Jahn-Teller (JT) distortions and has been applied to study the elastic response of the LaMnO3 structure to defects in the JT ordering. Surprisingly, antiphase domain boundary defects in the pattern of ordered JT octahedra, along the [110] and [110] bonding directions, are found to produce 1D stripe patterns rotated 45 degrees along a* directions, similar to stripe structures observed in these systems. Geometric simulation is shown to be an efficient and powerful approach for finding relaxed atomic structures in the presence of disorder in networks of corner-shared JT-distorted octahedra such as the perovskites. Geometric modeling rapidly relaxes large supercells (thousands of octahedra) while preserving the local coordination chemistry, and shows great promise for studying these complex systems.